ENDEMIC MEDICINAL PLANT SPECIES DISTRIBUTED IN JIZZAKH REGION - Ochilov Azizjon Shukhrat ugli,Jurayeva Iroda Muminovna (Ethiopian International Journal of Multidisciplinary Research, 2025)
The medicinal plants in common endem jizzakh region are studied in this article. Endem of medicinal plants found not only the wealth of the local ecological system, but also in folk medicine is one of the invaluable resources as important. The biological properties of medicinal plants research common in jizzakh region, ecological role, and be applied in folk medicine in their system that contains information about.